INVESTMENT DECISIONS OF WOMEN ENTREPRENEURS: A CASE STUDY IN KAMRUP(M) DISTRICT OF ASSAM - Kedia, Richika; Banik, Gour Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Investment decisions are a critical component of financial management and directly influence the sustainability and growth of enterprises. For women entrepreneurs, who often face financial and socio-cultural challenges, investment choices reflect both their risk-taking capacity and strategic priorities. This study focuses exclusively on the investment decisions of women entrepreneurs in Kamrup(M) district of Assam. Data was collected from 60 women entrepreneurs registered under the District Industries & Commerce Centre (DICC), Kamrup, through structured questionnaires and interviews. The findings reveal that women entrepreneurs demonstrate a diversified investment portfolio. Equal proportions invest in mutual funds/SIPs, shares, and real assets such as gold and real estate, while a smaller group prefers defensive investments, government securities, and bank deposits. In terms of expenditure allocation, significant amounts are directed toward direct materials and overheads, whereas labour expenses remain comparatively lower. This indicates a preference for investments that directly contribute to business growth and operational efficiency. By analyzing investment avenues and expenditure allocation patterns, this study highlights the emerging trend of women entrepreneurs shifting from conservative investments to more growth-oriented options. The results underline the need for financial literacy programs, improved access to investment advisory services, and awareness campaigns to empower women in making informed investment decisions.